2020
DOI: 10.1002/jpen.1775
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomics of Parenteral Nutrition with ω‐3 Fatty Acids in Hospitalized Adults

Abstract: The inclusion of ω‐3 fatty acids as part of parenteral nutrition is associated with clinical benefits such as a reduced likelihood of infectious complications and shorter hospital and intensive care unit (ICU) stays. As healthcare resources are limited, pharmacoeconomic analyses have been performed, typically modeling studies, using cost and outcomes data to investigate the cost‐effectiveness of parenteral nutrition regimens including ω‐3 fatty acids from fish oil compared with standard parenteral nutrition wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 33 publications
0
14
0
3
Order By: Relevance
“…Mortality was lower with 16%, but the difference did not reach significance (20 studies: RR 0.84, 95% CI 0.65 to 1.07; p = 0.15) [216]. Moreover, fish oil was found to be more cost-effective than parenteral nutrition with a standard intravenous lipid emulsion [220].…”
Section: Omega-3 Lcpufas In Critically Ill Surgical Patientsmentioning
confidence: 94%
“…Mortality was lower with 16%, but the difference did not reach significance (20 studies: RR 0.84, 95% CI 0.65 to 1.07; p = 0.15) [216]. Moreover, fish oil was found to be more cost-effective than parenteral nutrition with a standard intravenous lipid emulsion [220].…”
Section: Omega-3 Lcpufas In Critically Ill Surgical Patientsmentioning
confidence: 94%
“…Thus, the cost-effectiveness of various IV lipid emulsions is an important consideration when assessing therapeutic options, 121,122 and so these pharmacoeconomic aspects have also been reviewed in this supplement. 123 Discrete-event simulation models that incorporate evidence-based clinical data and cost estimates derived from local sources are recognized as a useful method for evaluating health economic outcomes. 124,125 Pharmacoeconomic evaluations comparing lipid emulsions containing ω-3 fatty acids with standard lipid emulsions in critically ill and surgical populations have shown that using IV lipid emulsions containing ω-3 fatty acids is a cost-effective strategy in patients who require PN.…”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
“…The management of patients who require PN represents a substantial source of healthcare resource consumption. Thus, the cost‐effectiveness of various IV lipid emulsions is an important consideration when assessing therapeutic options, and so these pharmacoeconomic aspects have also been reviewed in this supplement . Discrete‐event simulation models that incorporate evidence‐based clinical data and cost estimates derived from local sources are recognized as a useful method for evaluating health economic outcomes …”
Section: Pharmacoeconomic Considerationsmentioning
confidence: 99%
“…肠外营养更易 改善营养状况, 在疾病治疗和帮助患者成功脱离呼吸 机方面也有积极作用, 有助于患者渡过危险期, 促进 康复 [55,63] , 但要实时监测代谢状况, 动态调整给予量, 防止过度喂养 [64] . , 改善 气体交换 [66] , 降低感染并发症, 缩短住院时间及ICU时 间, 同时表现出显著的卫生经济效益 [67] . ω-6:ω-3=2.1:1 的免疫中性效应可延长移植器官的存活时间 [68] .…”
Section: 肠外营养unclassified